Sustainable energy landscapes designing, planning, and development - Stremke, Sven; Dobbelsteen, Andy van den (Applied ecology and environmental management : a series / series editor, Sven E. Jorgensen, 2013)
"With experts from different related fields discussing their approaches to energy-conscious planning and design, this comprehensive book presents state-of-the-art research, education, and design practice with respect to sustainable energy landscapes. It also addresses how to quantify the impact of energy transition both on landscape quality and energy economy, issues of growing importance. Focusing on the municipal and regional scale, where energy-conscious interventions are effective and stakeholders can participate actively in the transition process, the text illustrates practical applications of emerging methods using case studies from across the globe"--Provided by publisher.